1998
DOI: 10.1080/00103629809370093
|View full text |Cite
|
Sign up to set email alerts
|

Use of non‐contacting electromagnetic inductive method for estimating soil moisture across a landscape

Abstract: There is a growing interest in real-time estimation of soil moisture for site-specific crop management. Non-contacting electromagnetic inductive (EMI) methods have potentials to provide real-time estimate of soil profile water contents. Soil profile water contents were monitored with a neutron probe at selected sites. A Geonics LTD EM-38 terrain meter was used to record bulk soil electrical conductivity (EC A ) readings across a soil-landscape in West central Minnesota with variable moisture regimes. The relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(28 citation statements)
references
References 5 publications
2
25
0
1
Order By: Relevance
“…Soil pH, sampling sites. As per other reports (Kachanoski et al, 1988;Khakural and Robert, 1998), positive correlations which typically shows a strong relationship with EC 1:1 (Patriquin et al, 1993), was also significantly different were found between EC a and clay content (Table 3), with clay content ranging between 12.2 and 38.8 % in among EC a classes in deep (0-30 cm) soils.…”
Section: Resultssupporting
confidence: 63%
See 1 more Smart Citation
“…Soil pH, sampling sites. As per other reports (Kachanoski et al, 1988;Khakural and Robert, 1998), positive correlations which typically shows a strong relationship with EC 1:1 (Patriquin et al, 1993), was also significantly different were found between EC a and clay content (Table 3), with clay content ranging between 12.2 and 38.8 % in among EC a classes in deep (0-30 cm) soils.…”
Section: Resultssupporting
confidence: 63%
“…Substantial research effort has been directed and for spatially delineating soil physical, chemical, and biological properties (0-to 7.5-and 0-to 30-cm depths) toward understanding location-specific relationships between EC a and those factors contributing to its measurerelated to yield and ecological potential. This information is essential for monitoring the impact of management, including moisture (Khakural and Robert, 1998;Sheets and Hendrickx, 1995;Kachanoski et al, 1988), ment on temporal trends in soil condition and for the successful implementation of site-specific management. salinity (Lesch et al, 1992;Rhoades and Corwin, 1981;Rhoades and Ingvalson, 1971), and salinity and clay content (Williams and Hoey, 1987).…”
mentioning
confidence: 99%
“…High-intensity or first-order soil mapping based on EMI is offered commercially in many countries to provide information on the distribution and variability of soils at field and landscape scales Khakural et al, 1998;King et al, 2005;Korsaeth et al, 2008;Kravchenko, 2008;Weller et al, 2007). Recently, EMI has also been used to improve the quality of several first-order soil maps (Anderson-Cook et al, 2002;Doolittle et al, 2008Doolittle et al, , 2009Farahani and Flynn, 2007;White et al, 2012).…”
Section: Refine and Improve The Quality Of Soil Mapsmentioning
confidence: 99%
“…Apparent conductivity has also been used as a surrogate measure of soil water content (Allred et al, 2005;Brevik et al, 2006;Hezarjaribi and Sourell, 2007;Huth and Poulton, 2007;Kachanoski et al, 1988Kachanoski et al, , 1990Khakural et al, 1998;Korsaeth et al, 2008;Mueller et al, 2003;Sheets and Hendrickx, 1995;Tromp-van Meerveld and McDonnell, 2009;Waine et al, 2000), soil texture (Heil and Schmidhalter, 2012;James et al, 2003;Saey et al, 2012a;White et al, 2012); and clay content (Cockx et al, 2009;Harvey and Morgan, 2009;King et al, 2005;Mueller et al, 2003;Sommer et al, 2003;Weller et al, 2007;Wienhold and Doran, 2008;Williams and Hoey, 1987). Electromagnetic induction has been used to assess difference in lithology and mineralogy (Bourgault and Rabenhorst, 2012;Doolittle et al, 2005Doolittle et al, , 2013, soil compaction (Al-Gaadi, 2012; Sudduth et al, 2010); CEC (Korsaeth et al, 2008;Triantafilis et al, 2009;), exchangeable Ca and Mg (McBride et al, 1990), CaCO 3 (Vitharana et al, 2008b); soil pH (Bianchini and Mallarino, 2002;Dunn and Beecher, 2007;Van Meirvenne et al, 2013;Vitharana et al, 2008b;Wienhold and Doran, 2008), soil organic carbon …”
Section: Other Soil Propertiesmentioning
confidence: 99%
“…EM38 and EM31). In contrast, Khakural et al (1998) obtained relatively poor relationships between EC a and moisture content for vertical and horizontal measurement modes of EM38. It appears that the relationship between soil water content and EC a may be affected by other soil properties (e.g.…”
Section: Introductionmentioning
confidence: 83%